2014
DOI: 10.1186/1748-717x-9-187
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional tumor failure after definitive radiation for patients with stage III non-small cell lung cancer

Abstract: BackgroundLocoregional tumor failure (LRF) after definitive chemoradiation for patients with stage III NSCLC remains unacceptably high. This analysis sought to further define where LRF occurs relative to radiation dose received and pre-treatment PET scan-defined maximum standard uptake value (SUVmax).MethodsThis was a retrospective study analyzing patients with stage III NSCLC treated with definitive radiation between 2006 and 2011. LRF was defined as failure within the ipsilateral lung, hilum or mediastinum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…We adopted this SBRT boost strategy because approximately 60% of local regional recurrences after conventional chemoradiation involve the mediastinum. 16 In our study, the MTD of a SBRT boost after 44 Gy of conventionally fractionated thoracic radiation with concurrent chemotherapy was 6 Gy  5, with SBRT delivered to residual nodal and primary disease. Additionally, a SBRT boost dose of 10 Gy  2 was well tolerated, with no grade 3 or higher treatment-related AEs.…”
Section: Discussionmentioning
confidence: 64%
“…We adopted this SBRT boost strategy because approximately 60% of local regional recurrences after conventional chemoradiation involve the mediastinum. 16 In our study, the MTD of a SBRT boost after 44 Gy of conventionally fractionated thoracic radiation with concurrent chemotherapy was 6 Gy  5, with SBRT delivered to residual nodal and primary disease. Additionally, a SBRT boost dose of 10 Gy  2 was well tolerated, with no grade 3 or higher treatment-related AEs.…”
Section: Discussionmentioning
confidence: 64%
“…The latter showed that biologically equivalent dose (BED) and local control were associated with overall survival. It is known that local control after chemoradiation (60 Gy) is not optimal [44][45][46][47][48], but dose escalation to 74 Gy did not show the anticipated improvements [28] and was primarily associated with increased cardiopulmonary mortality due to higher doses delivered to these organs at risk. On the basis of these considerations, a reirradiation dose of 60-66 Gy can be prescribed if sufficient sparing of organs at risk can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Several planning studies examined the potential benefits of incidental nodal irradiation of uninvolved lymph node regions when using 3D-CRT [ 7 , 8 , 20 , 21 ]. Even with PET-based IF-RT of stage III NSCLC, rates of out-of-field nodal recurrences can be as high as 10 % and therefore cannot be considered as insignificant [ 22 ]. It is controversial if these recurrences can be attributed either to the small a priori risk of microscopic involvement in elective nodal regions or the benefits of incidental nodal irradiation.…”
Section: Discussionmentioning
confidence: 99%